STRUKTUR CERITA CALON ARANG KARYA PRAMOEDYA ANANTA TOER: KAJIAN STRUKTURALISME LÉVI-STRAUSS - Naila Nilofar (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Cerita Calon Arang is a folktale that is retelling by Pramoedya Ananta Toer in a story book to save memory about the folktale. This research is aimed to reveal the structure of Pramoedya Ananta Toer’s Cerita Calon Arang by Lévi-Strauss Structuralism approach. The result of the research shows that there are paired opposition and elements that unite the pairs in a serie of mytheme. After looking at the relation between mythemes, there is a deep structure in Cerita Calon Arang. The deep structure of the story shows that myth of Cerita Calon Arang is used as a media of entering Hindu religion in east Java kingdom.